Merespon Gentrifikasi: Perancangan Homestay R09 dan Wisata Komunitas di Kawasan Between Two Gates - Mutiara, Maffyra Binar Firstya; Nurkukuh, Dwi Kunto (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Kotagede, as a heritage district rich in historical value, is experiencing ongoing gentrification due to changes in ownership, building functions, and tourism development. One strategic area within this district is Between Two Gates, which holds architectural and social potential as a community-based special interest tourism destination. This community service project focuses on redesigning the long-abandoned Rumah R09 into a homestay through an adaptive reuse approach, aiming to preserve cultural heritage while improving local welfare. The methods include field observation, traditional architectural analysis, spatial needs assessment, and context-sensitive design planning. The result is a homestay concept that retains traditional values, supports communal activities, and serves as a participatory strategy to address gentrification in heritage areas.